Die Wirksamkeitsforschung von systemischer Therapie/Familientherapie: Zeitbezogene Trends und Unterschiede in der Qualität von Studien zu verschiedenen Behandlungsmodellen - Inge Seiffge-Krenke; Stefan Beher; Christian Skaletz (Journal of Family Research, 2007)
Sixty-eight studies investigating the effectiveness of systemic/family therapy for children and adolescents (published from 1973 to 2004) were analyzed to determine whether quality differences exist between studies of more integrative versus classically-orien¬tat¬ed systemic family therapy. These differences were examined with respect to the type of therapy model investigated, publication year, and origin of publication. Results indicate that, based on the consideration of important methodological criteria (e.g., existence of a control group, randomized study design, registration of clinical outcome), integrative family therapy is more effective than classic family therapy. Additional ana¬lyses revealed that the year and origin of publication predicted a high methodological standard, independent of family therapy orientation. The analyses also revealed that although the number of evaluation studies on systemic/family therapy has considerably increased, especially in the USA, comparable studies on German samples are lacking.